The Influence of Market Orientation on Marketing Performance Through Absorptive Capacity in Food and Beverage SMEs in Sidoarjo - Nuriya Sinta Dewi; Muhafidhah Novie; Laily Muzdalifah; Cynthia Eka Violita (Islamic Business and Management Journal, 2025)
This study aims to analyze the effect of Market Orientation on Marketing Performance through Absorptive Capacity in the food and beverage MSME sector in Sidoarjo. The research method used is quantitative with an explanatory research approach. Data were collected through a survey of 216 MSMEs selected using a purposive sampling technique. Data analysis was conducted using the SEM-PLS method with Smart PLS 4.0. The results show that Market Orientation has a positive and significant effect on Marketing Performance. Furthermore, Market Orientation also positively influences Absorptive Capacity, which in turn enhances Marketing Performance. These findings confirm that Absorptive Capacity plays a significant mediating role in the relationship between Market Orientation and Marketing Performance. Thus, increasing market orientation in MSMEs can strengthen competitiveness and improve overall marketing performance.